Analysis of Public Services for Receiving Complaints at The Integrated Police Service Center of The Bali Region - Swandi, Recky Tanzillazil Rachim; Mahendra, I Made Agus; Widyantari, Ni Luh Putu (Journal Of Social Science (JoSS), 2024)
This research analyzes public services related to receiving complaints at the Integrated Police Service Center (SPKT) in the Bali Region. SPKT serves as the frontline for the Indonesian National Police, which emphasizes the importance of effective complaint handling to gain the trust of the public. This study aims to evaluate service delivery through indicators such as response time, clarity of procedures, and officer professionalism. Using a qualitative approach, data was collected through interviews, observations, and document studies. The main findings show that although most respondents expressed satisfaction with the SPKT service, there are still some significant obstacles, including a lack of public understanding of the complaint procedure, limited facilities, and inadequate use of technology. These factors hinder effective service delivery and impact on public trust in the police. This study highlights the need for increased efforts, especially in socializing complaint procedures, optimizing the use of technology, and providing training for responsive and efficient services. Recommendations for Polri include improving communication strategies and infrastructure to better serve the community. Ultimately, this study contributes to the ongoing discourse to improve public services in law enforcement, aiming to foster greater community satisfaction and trust in the police institution.